2021
DOI: 10.1002/pld3.338
|View full text |Cite
|
Sign up to set email alerts
|

Rice aquaporin OsPIP2;2 is a water‐transporting facilitator in relevance to drought‐tolerant responses

Abstract: In rice ( Oryza sativa ), the PLASMA MEMBRANE INTRINSIC PROTEIN (PIP) family of aquaporin has 11 members, OsPIP1;1 to OsPIP1;3, and OsPIP2;1 to OsPIP2;8, which are hypothesized to facilitate the transport of H 2 O and other small compounds across cell membranes. To date, however, only OsPIP1;2, OsPIP2;1, and OsPIP2;4 have been demonstrated for substrate selectivity in their source plant (rice). In this study, OsPIP2;2 was characterized as the most efficient fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…In the roots of date palms, the expression of PdPIP1-1, PdPIP1-3, and PdPIP2-2 was induced during early drought [49]. Similar results were obtained for rice, where OsPIP2-2 showed higher expression under drought stress and CrPIP2-3 from bay bean (Canavalia rosea) also fit the expression pattern in transgenic plants [50,51]. Another research study found that SIPIP2-5, SIPIP2-7, and SIPIP2-1 were highly expressed in the roots [52].…”
Section: Discussionsupporting
confidence: 76%
“…In the roots of date palms, the expression of PdPIP1-1, PdPIP1-3, and PdPIP2-2 was induced during early drought [49]. Similar results were obtained for rice, where OsPIP2-2 showed higher expression under drought stress and CrPIP2-3 from bay bean (Canavalia rosea) also fit the expression pattern in transgenic plants [50,51]. Another research study found that SIPIP2-5, SIPIP2-7, and SIPIP2-1 were highly expressed in the roots [52].…”
Section: Discussionsupporting
confidence: 76%
“…The AQPs primarily participate in maintaining cellular water homeostasis (Wang et al., 2020; Zargar et al., 2017). OsPIP2;2 is a predominant facilitator of water transport with relevance to drought tolerance (Bai et al., 2021). Transgenic tomato plants ectopically expressing MdPIP1;3 exhibit more engorged guard cells and closed stomata than WT plants, thereby enhancing their drought tolerance (Wang et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of ZmPIP1;1 , ZmPIP1;5 and ZmPIP2;4 from Zea mays (maize) was transiently induced in the outer root tissue when maize plants regained osmotic potential following a mild salt treatment, thus suggesting that they might play a role in cellular water transport (Zhu et al., 2005). OsPIP2;2 from Oryza sativa (rice) mediates H 2 O transport in response to drought stress (Bai et al., 2021). Furthermore, the endoplasmic reticulum (ER) membrane‐anchored E3 ligase Rma1H1 was found to mediate the degradation of PIP2;1, leading to less trafficking of PIP2;1 from the ER to the PM and increasing drought tolerance in Arabidopsis (Lee et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…OsPIP1;3, responds strongly to drought stress and can be recruited to the plasma membrane by OsPIP2;2, to be a water‐transporting facilitator (Lian et al., 2004; Liu et al., 2020). Recent research has revealed the highest water transporting activity of OsPIP2;2 among the 11 PIPs in rice, which is beneficial to enhance the drought tolerance in rice protoplasts and seedlings (Bai et al., 2021). SIPs had a moderate water transport activity (Maurel et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, there are total 33 AQPs (Sakurai et al., 2005). Some of them had been found to respond to drought (Bai et al., 2021; Lian et al., 2004), while the underlying regulation mechanism is unclear. Since AQPs are closely related to plant water status, regulation of rice AQPs might play a role in drought resistance.…”
Section: Introductionmentioning
confidence: 99%